Benign and malignant breast diseases during pregnancy and lactation: a diagnostic challenge - Rahim, Anila; Mahnoor Hafeez; Amjad Sattar; Waqas Ahmed Farooqui (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the incidence of breast cancer associated with pregnancy and lactation, and to evaluate the lesions on ultrasound. Method: The descriptive, observational study was conducted at the Dow Institute of Radiology, DUHS, Karachi from December 2020 to August 2021, and comprised pregnant and lactating women with clinically palpable breast lumps and/or painful breast. The margins, orientation, echo pattern and associated features of the lesions were studied on ultrasound and were assigned a Breast Imaging Reporting and Data System grade. All the lumps were followed and ultrasound-guided core needle biopsy for histopathology was done of grades IV and V cases. Incidence and Accuracy of ultrasound for diagnosis of pregnancy-associated breast cancer was estimated. Data was analysed using SPSS 26. Results: Of the 237 women, 19(8%) were pregnant and 218(92%) were lactating. The overall mean age was 28.4±5.5 years. Ultrasound findings for lactating and pregnant women were significantly different (p=0.05). Significant association of Breast Imaging Reporting and Data System grades III, IV and V lesions with heterogeneous echo texture of mass was seen (p<0.001). Biopsy was performed in 20(8.4%) cases, and 12(60%) of them had benign results on histopathology. Conclusion: A variety of benign and malignant breast diseases were found in women during pregnancy and lactation phases. Key Words: Pregnancy, Breast cancer, Lactation, Diagnosis, Ultrasound, Core biopsy.